Impact of the Spatial Organization of Bifunctional Metal–Zeolite Catalysts on the Hydroisomerization of Light Alkanes. (22nd January 2020) - Cheng, Kang; van der Wal, Lars I.; Yoshida, Hideto; Oenema, Jogchum; Harmel, Justine; Zhang, Zhaorong; Sunley, Glenn; Zečević, Jovana; de Jong, Krijn P.
Abstract: Improving product selectivity by controlling the spatial organization of functional sites at the nanoscale is a critical challenge in bifunctional catalysis. We present a series of composite bifunctional catalysts consisting of one‐dimensional zeolites (ZSM‐22 and mordenite) and a γ‐alumina binder, with platinum particles controllably deposited either on the alumina binder or inside the zeolite crystals. The hydroisomerization of n ‐heptane demonstrates that the catalysts with platinum particles on the binder, which separates platinum and acid sites at the nanoscale, leads to a higher yield of desired isomers than catalysts with platinum particles inside the zeolite crystals. Platinum particles within the zeolite crystals impose pronounced diffusion limitations on reaction intermediates, which leads to secondary cracking reactions, especially for catalysts with narrow micropores or large zeolite crystals. These findings extend the understanding of the "intimacy criterion" for the rational design of bifunctional catalysts for the conversion of low‐molecular‐weight reactants. Abstract : Am richtigen Ort : Bifunktionelle Katalysatoren mit Platin‐Partikeln in der Aluminiumoxid‐Schicht, welche die aktiven Platin‐ und Säure‐Zentren auf nanoskaliger Distanz hält, zeigen eine höhere Ausbeute der gewünschten Isomere als Katalysatoren, bei denen sich die Platin‐Partikel in den Zeolith‐Kristallen befinden.